Apparent molar volumes of sodium naproxen in water at several concentrations and temperatures (2023)
Densities of aqueous solutions of sodium naproxen have been measured as functions of concentration (from 0.0250 to 0.5000 mol kg-1) and temperature (from 278.15 to 313.15 K). The apparent molar volumes, partial molar volumes at infinite dilution and part